The association between obesity and hematologic inflammatory markers in the first trimester pregnancies - İncesu Çintesun, Feyza Nur (Perinatal Medicine Foundation, 2020)
Objective Obesity is the defined as the abnormal or excessive accumulation of the fat which is harmful for the health, and its prevalence has been increasing. Many studies have shown that obesity alone leads to inflammation and causes poor gestational outcomes. In our study, we aimed to investigate the association between basic hematologic markers and obesity in the first trimester pregnancies. Methods A total of 321 pregnant women who admitted to the clinic of gynecology and obstetrics in a tertiary state hospital were included in the study. The patients were separated into three groups, which were normal weight (BMI: 18-24.9 kg/m2), overweight (BMI: 25-29.9 kg/m2), and obese (BMI>30 kg/m2). Of the patients, the demographic data (age, gravida, and parity) and the parameters of hemoglobin, hematocrit, white blood cell, neutrophil, lymphocyte, platelet (PLT), eosinophil, basophil, mean platelet volume (MPV), platelet distribution width (PDW), neutrophil/lymphocyte ratio (NLR), red blood cell distribution width (RDW), plateletcrit (PCT) and platelet/lymphocyte ratio (PLR) measured in the complete blood count which was checked in the first trimester routinely during the pregnancy follow-up were analyzed. The three groups were compared in terms of inflammatory markers. Results The patients were evaluated in three groups: 108 patients with normal weight (Group 1), 109 overweight patients (Group 2) and 104 obese patients (Group 3). No significant difference was found in terms of age, parity and gravida when the demographic data were analyzed among the groups (p>0.05). When the groups were compared in terms of hematologic markers, similar values were found in the markers other than white blood cell, neutrophil, lymphocyte, PLT and PCT values. The difference among white blood cell, neutrophil, lymphocyte, PLT and PCT values were between the patients with normal weight and obese patients, and the values of these markers were found higher in overweight / normal weight patient groups than the normal group (p<0.05). Conclusion The values of white blood cell, neutrophil, lymphocyte, PLT and PCT which were shown to be associated with inflammation were higher in the obese patients.